Perancangan Perubahan Visual Logo Dan Kemasan Umkm Belle Crochet Di Manado Untuk Meningkatkan Daya Tarik Konsumen - Muhammad Rafqi Risdiansyah (CV. ITTC INDONESIA, 2025)
Packaging and visual branding play a crucial role in shaping a product's image and attracting consumer attention, especially for MSMEs in the creative sector. Belle Crochet, a knitting craft MSME, has high product potential but faces challenges in the visual consistency of its brand identity, including its logo, packaging design, and social media aesthetics. This activity used a participatory approach and design thinking methods to help Belle Crochet improve the visual quality of its packaging and branding. Observations and design results showed that the new packaging design, which is more aesthetic, informative, and reflects the product's character, successfully increased consumer appeal and strengthened perceptions of professionalism. This activity demonstrates that visual design assistance is an effective strategy for increasing the competitiveness of local craft MSMEs.